EVALUASI PELAKSANAAN PROGRAM PRAKTIK KERJA LAPANGAN (PKL) PADA SMK MUHAMMADIYAH 2 TANGERANG - Shintawati Shintawati; Nurul Anriani (KABILAH : Journal of Social Community, 2022)
Abstrak The purpose of this study was to evaluate Fieldwork Practice Program (PKL) at SMK Muhammadiyah 2 Tangerang. This study uses a qualitative approach. This study was conducted at the SMK Muhammadiyah 2 Tangerang. The phenomenon studied was the implementation of PKL activities in 2022, from January to March. The evaluation model used is CIPP (context, input, process, and product). Data retrieval techniques included interviews, observations, and documentation. The results showed that, in the context aspect, PKL applied the principle of goal formulation based on needs and situations. In the input aspect, PKL activities have carried out good and appropriate resource management, as well as accurate and efficient target-oriented funding calculations. In the process aspect, PKL activities have been carried out properly by adhering to existing procedures and are neatly documented. In terms of products, PKL activities reached the specified target. Keywords: Evaluation, Fieldwork Practice Program (PKL), CIPP